ANALISIS PERKEMBANGAN SOSIAL EMOSIONAL ANAK BERKEBUTUHAN KHUSUS (AUTISME) DI SKH 02 AL-IHSAN CILEGON - Nurul Wihdahtul Ummah; Yahdinil Firda Nadhirah (STKIP Subang, 2024)
This article analyzes the socio-emotional development of children with special needs with autism in SKh 02 Al-Ihsan. With a focus on a child with the initials